A socio-economic assessment of the interaction between cruise tourism and land-based tourism in Isafjordur, Iceland - Renita, Lucian, 1984- (2014)
Læst til 28.5.2015 Historically, Isafjordur (population 2500), the main town of the Westfjords region of Iceland, has been a fishing town, but in recent years, tourism has become increasingly important, developing around the rich natural and cultural heritage of the area. Both land-based and cruise tourism have increased, but cruise tourism has increased much faster, with the passenger capacity of the larger cruise-ships matching and even exceeding the population of the town itself. Cruise tourism typically has the characteristics of mass tourism, and brings less income than land-based tourism, while bearing a number of hidden costs, some of which are associated with negative impacts on the experience of land-based tourists. This raises a number of issues regarding the capacity of the town to accommodate both cruise and land-based tourists, and the way in which these two segments interact, particularly how and whether cruise tourism impacts land-based tourism operations, and what kind of development of cruise tourism is desirable for the town if any at all, such that the town economy benefits most. Research methods included surveys of the international land-based tourists to Isafjordur and local businesses, semi-structured interviews with local businesses and experts, and an analysis of both primary and of secondary data from surveys and interviews and from the official records of the harbour authorities. Results showed that cruise tourism has both positive and negative impacts on land-based tourism, although at the current level of cruise tourism, the negative impacts were rather low, with the main issues arising from competition for similar services for cruise and land-based tourists. Cruise tourism likely had a lower direct economic impact than land-based tourism, and lower spending per tourist. However, while larger cruise-ships generated an overall higher income, smaller cruise-ships tended to generate higher income per passenger, both for the harbour and for the local businesses, with fewer negative ...